2019
DOI: 10.3389/fgene.2019.01311
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure and Genetic Diversity of Sheep Breeds in the Kyrgyzstan

Abstract: Sheep are a main livestock species of Kyrgyzstan, a Central Asian country with predominating mountain terrain. The current gene pool of local sheep resources has been forming under diverse climate conditions from the era of the trading caravans of the Great Silk Road, through the Soviet period of large-scale livestock improvements, which was followed by the deep crisis at the end of the 20th century, up to now. However, not much is known about the genetic background and variability of the local sheep populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
33
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 54 publications
9
33
2
Order By: Relevance
“…These findings are consistent with previous research on sheep 38 , 39 , 3 , 40 , which showed that individuals were separated by global population structure patterns according to their geographical origin.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are consistent with previous research on sheep 38 , 39 , 3 , 40 , which showed that individuals were separated by global population structure patterns according to their geographical origin.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have elucidated that using genomic data to evaluate the extent of inbreeding was more accurate than using pedigree data ( Purfield et al, 2012 ; Zanella et al, 2016 ) because the pedigree data were always incomplete and failed to capture the influence of relatedness among individuals in the population. The level of ROH reflects the ancient and recent inbreeding history of a population, which has been widely applied to explore the extent of inbreeding in the population of any species ( Deniskova et al, 2019 ; Xu et al, 2019 ; Bhati et al, 2020 ). As shown in previous report, the average ROH levels varied considerably among Chinese pigs, ranging from the lowest value of 20.6 Mb in wild boars to the largest value of 168 Mb in DSE pigs ( Wang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…For both genotyping methods, we calculated the genomic relationship matrix as previously described taking into consideration SNPs with call rate ≥ 0.9 and MAF ≥ 0.05. The principal component analysis was used to infer population differentiation [ 28 , 29 ]. The heat map of genomic relationships was generated with the software RStudio Team [ 30 ] (File S2).…”
Section: Methodsmentioning
confidence: 99%